2020
DOI: 10.1186/s12884-020-2856-8
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine use and predictors among pregnant women attending antenatal care in Ethiopia: a systematic review and meta-analysis

Abstract: Background: The use of herbal medicine among pregnant women is increasing in many low-and high-income countries due to their cost-effectiveness in treatment and ease of access. Research findings across Ethiopia on the prevalence and predictors of herbal medicine use among pregnant women attending antenatal care are highly variable and inconsistent. Therefore, this systematic review and meta-analysis aims to estimate the overall prevalence of the use of herbal medicine and its predictors among pregnant women at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 46 publications
(53 reference statements)
1
43
1
Order By: Relevance
“…22 A systematic review and meta-analysis also reported a high prevalence of self-medication. 23,24 This was due to poor awareness of pregnant women regarding medicines, 17,25 selling of prescription medications without prescription and loose regulatory system. 26 The prevalence of herbal medicine use was 111 (49.8%; 95% CI: 43%-58%).…”
Section: Discussionmentioning
confidence: 99%
“…22 A systematic review and meta-analysis also reported a high prevalence of self-medication. 23,24 This was due to poor awareness of pregnant women regarding medicines, 17,25 selling of prescription medications without prescription and loose regulatory system. 26 The prevalence of herbal medicine use was 111 (49.8%; 95% CI: 43%-58%).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is likely to be since Addis Ababa is the capital city of Ethiopia and the population of Tigray is smaller, mothers are more educated than others in Amhara and Oromia, and standard of maternal follow-up care is more available to regions that do not have a large number of mothers. They have a better understanding of the side effects of drugs taken during pregnancy, and mothers living in the capital are better off in terms of community wellbeing [61]. Another reason for the relatively small amount of non-prescribed drug usage by pregnant mothers in the Tigray region is the small amount of research from the Tigray region included in this research.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation for this could be that these medicines have been obtained from pharmacies or drugstores. The use of over-the-counter painkillers is easy without prescription, as most pregnancy-related pain is associated with headaches and the cost of medicines is cheap [61].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of the medicinal plants commonly used by pregnant women includes Zingiber officinale , Allium sativum , Ocimuml amiifolium , Eucalyptus and Rutachalepensis , etc. [ 40 ]. For example, the usage of Clivia miniata has been reported to be associated with some side effects such as salivation and diarrhoea while Callilepis laureola causes confusion, convulsion, hepatic, and renal failures.…”
Section: Safety Of Traditional Herbal Medicinesmentioning
confidence: 99%